2012
DOI: 10.1128/aac.01489-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posaconazole on Cyclosporine Blood Levels and Dose Adjustment in Allogeneic Blood and Marrow Transplant Recipients

Abstract: eThe posaconazole prescribing information recommends an upfront cyclosporine dose reduction upon initiation of posaconazole prophylaxis. We examined this recommendation in the early phase of allogeneic transplantation, where cyclosporine levels potentially becoming subtherapeutic following upfront dose reduction would be deleterious to transplant outcome. Our data show that while posaconazole leads to an increase in cyclosporine levels, subsequent cyclosporine dose reduction can be safely guided by therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Another pharmacokinetic analysis showed that a CsA dose reduction of up to 50 % was necessary with concomitant posaconazole treatment [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Another pharmacokinetic analysis showed that a CsA dose reduction of up to 50 % was necessary with concomitant posaconazole treatment [36]. …”
Section: Discussionmentioning
confidence: 99%
“…In the presence of p o s a c o n a z o l e , p l a s m a c o n c e n t r a t i o n s o f t h e s e immunosuppressants are substantially increased [15,16,17] and this increase is associated with adverse events [15,18]. The increase in exposure of immunosuppressants in the presence of posaconazole requires adjustment of the dose of the immunosuppressant to sustain the therapeutic levels of the drug and reduce adverse events associated with increased immunosuppressant concentrations [13,20,21]. The prescribing information for posaconazole recommends reducing the dose of cyclosporine by approximately 75% and the dose of tacrolimus approximately one-third of the original dose upon initiation of posaconazole treatment [19].…”
mentioning
confidence: 99%
“…administration. Temporal pattern of CsA level changes due to institution or discontinuation of co-medicating azole has been observed to be within days to few weeks [115][116][117]. Another common antifungal in this setting, micafungin, showed no interacting effect [118].…”
Section: Interactionsmentioning
confidence: 95%
“…It seems that voriconazole is the strongest metabolic inhibitor of CsA among common azole antifungals used in HSCT although specifically designed studies for head to head comparison in this setting are lacking. Itraconazole and posaconazole also increase CsA exposure regarding trough, peak and AUC values but maybe to a lower extent than voriconazole [18,21,115]. It has been stated that drug interaction for voriconazole or itraconazole and CsA is more detectable than fluconazole even by iv.…”
Section: Interactionsmentioning
confidence: 95%
See 1 more Smart Citation